Propuesta de un sistema de gestion de calidad basado en la norma internacional ISO 9001:2015 en la empresa DST ACADEMY - Vallejo Carriel, Carlos Fabian (2018)
This research project seeks the design of a quality management system proposal based on the international standard ISO 9001:2015 for the DST Academy company, with the aim of improving the management of the company in the processes and service delivery. For this it was taken as a starting point to apply tools of analysis as they are the FODA, interview, in addition to a check List of verification with respect to the requirements that establishes the ISO 9001:2015, proceeding with the evaluation of the context of the company like Organization, its stakeholders, showing the environment in the company is unfolding. It was also determined the processes necessary for the design of the system of quality management, by means of characterization tokens, once determined and characterized the processes of the system were established procedures manuals according to the guidelines that sets the standard. It is concluded that the fulfillment of the company with respect to the requirements of this ISO update is not acceptable, nor meets its established requirements, this is evident in the applied Check List. The context of the Organization assessed by means of the interview, FODA analysis provides a broader and more concrete view of the company. The determination of the processes of the quality Management system in conjunction with the elaboration of manuals established a clearer, detailed view of the purpose of each of these detailed processes in the process map designed for the company. Keywords: Organization Context, Documentation, International Standard ISO 9001:2015, Quality Management System.